EFEKTIFITAS TEKNIK MASSASGE COUNTER PRESURE DAN TEKNIK RELAKSASI TERHADAP NYERI PERSALINAN KALA I FASE AKTIF PADA IBU PRMIGRAVIDA - Malinda, Aliyn; Dewi Lestari, Mega; Setya Roswendi, Achmad (Journal Healthcare Education, 2024)
Childbirth is the process of delivering a fetus, resulting in pain caused by contractions of the uterus muscles, which is felt in the lower back to the thighs. Untreated pain can lead to psychological and physiological problems for the mother. The intensity of labor pain during the first stage is mostly felt by primigravida mothers, higher compared to multiparous mothers. Efforts to reduce pain include massage counter-pressure techniques and relaxation techniques. The study employed a quasi-experimental research design with pretest-posttest methodology, utilizing quota sampling technique, The research sample consisted of 20 postpartum mothers who were primigravida. Data collection involved the use of the NRS measurement tool thought observation and the was analysed using the t-test as the data followed a normal distribution. The research findings indicated that the mean pain score before intervention was 8.88, which decreased to 5.05 after applying the massage counter pressure technique, while the mean pain score before intervention was 8.88 and after 8.65 using relaxation technique, Hence, it can be concluded that both massage counterpressure and relaxation techniques were effective in reducing pain, with a p-value of 0.001 Recommendations suggest that these techniques could be utilized to alleviate pain among postpartum mothers